1992
DOI: 10.1039/p29920000163
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance spectra of aliphatic ketyl radical anions in fluid solution

Abstract: Improved methods have been developed for generating aliphatic ketyl radical anions in solution for study by EPR spectroscopy. These methods involve either photolysis of a solution of potassium in the corresponding alcohol (which probably proceeds by initial electron transfer to the solvent), or abstraction of a hydrogen atom from the corresponding alcohol by photolytically generated tertbutoxyl radicals under strongly basic conditions. The EPR spectra of a number of new aldehyde and ketone radical ions are des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 18 publications
(3 reference statements)
0
13
0
Order By: Relevance
“…Because of the rather small inversion barrier, Johnson and Hudgens 1 concluded that H 2 COH effectively belongs to the C s (yz) point group having the inversion geometry, for which the electronic ground state corresponds to X 2 A′′. Experimental information about the structure and bonding of H 2 COH has been gained by analyzing the vibrational, 1,6 electronic, 1,7,8 photoionization, 9,10 and electron spin resonance (ESR) [11][12][13][14] spectra. The electronic spectrum, measured up to 6.0 eV, consists of Rydberg transitions only, assumed to be of type π* f 3s, 3p.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of the rather small inversion barrier, Johnson and Hudgens 1 concluded that H 2 COH effectively belongs to the C s (yz) point group having the inversion geometry, for which the electronic ground state corresponds to X 2 A′′. Experimental information about the structure and bonding of H 2 COH has been gained by analyzing the vibrational, 1,6 electronic, 1,7,8 photoionization, 9,10 and electron spin resonance (ESR) [11][12][13][14] spectra. The electronic spectrum, measured up to 6.0 eV, consists of Rydberg transitions only, assumed to be of type π* f 3s, 3p.…”
Section: Introductionmentioning
confidence: 99%
“…The ∆g av value of H 2 CO -, a radical isoelectronic with H 2 COH, is ∼500 ppm larger. 14 Krusic et al 12 studied the temperature dependence (from 148 to 215 K) of the β-proton hfcc and corresponding line shapes. On the basis of this information, they estimated a barrier height of ∼4.3 kcal/mol for the hindered rotation of OH about the CO bond, a value confirmed by ab initio results (see above).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations